Answer:
B
Explanation:
calculate the distance between A and B using the distance formula
d =
![\sqrt{(x_(2)-x_(1))^2+(y_(2)-y_(1))^2 }](https://img.qammunity.org/2023/formulas/mathematics/college/fnk6cf02e44j7tagae8yw19o2p6fivv23w.png)
with (x₁, y₁ ) = A (1, 6 ) and (x₂, y₂ ) = B (x, - 2 )
d =
![√((x-1)^2+(-2-6)^2)](https://img.qammunity.org/2023/formulas/mathematics/high-school/4fsblzmknvcqitgfqtjef4v77m5gmg7m8i.png)
=
![√((x-1)^2+(-8)^2)](https://img.qammunity.org/2023/formulas/mathematics/high-school/4j2qk48xkh3ho5yrchs07gc039uuc9tt1v.png)
=
![√((x-1)^2+64)](https://img.qammunity.org/2023/formulas/mathematics/high-school/q6ym9n2tvvurg5t2z0yu7zqtba5ttgbj5z.png)
given AB = 10, then equating gives
= 10 ( square both sides to clear the radical )
(x - 1)² + 64 = 10² = 100 ( subtract 64 from both sides )
(x - 1)² = 36 ← take square root of both sides
x - 1 = ±
= ± 6 ( add 1 to both sides )
x = 1 ± 6
then
x = 1 - 6 = - 5
x = 1 + 6 = 7
from the list then x = - 5 is a possible value